Prevalence of cardiovascular disease risk factors, health behaviours and atrial fibrillation in a Nepalese post-seismic population: a cross-sectional screening during a humanitarian medical mission - Adrega, Tiago; Ribeiro, Joana; Santos, Luis; Santos, Jose A (Nepalese Heart Journal, 2018)
Background and Aims: Nepal is a developing country with increasing rates of cardiovascular disease (CVD), and the recent 2015 earthquakes imposed critical social and epidemiological effects to the population. This study aims to assess the prevalence of CVD risk factors, social health behaviours and atrial fibrillation (AF) in a native population from a remote Nepalese village that was the epicentre of the May 2015 earthquake. Methods: Observational, cross-sectional study, addressing the population of dislodged inhabitants of Sindhupalchok. Data was collected during an opportunistic clinical screening in the midst of a humanitarian medical mission and consisted of demographic, anthropometric and medical data. Results: A total of 270 patients were assessed (41% in a temporary settlement with continuous organisational support and 59% in the remote village with less back-up). Among adults, 89% had low fruit consumption, 49% were overweight or had augmented waist circumference, 42% had smoking habits, 57% consumed alcohol regularly, 22% had high blood pressure measurements and 5% had abnormal glycaemic levels. An 11% prevalence of AF was found among the elderly. Conclusions: The studied population has a high prevalence of CVD risk factors, poor health behaviours and a significant prevalence of AF among the elderly representatives. International partnering and humanitarian work might be important tools to assess the population’s needs and implement corrective measures.